Chronic instability in a malformed tibiofibular syndesmosis associated with osteochondral lesion of the talus: a case report - Nishikawa, Danilo Ryuko Cândido; Romanholi, Pedro Bragato; Mann, Tânia Szejnfeld; Saito, Guilherme Honda; Duarte, Fernando Aires; Prado, Marcelo Pires (Journal of the Foot & Ankle, 2023)
Surgical treatment of tibiofibular syndesmosis (TFS) with chronic instability aims to obtain a solid and stable joint to avoid ankle arthritis. Osteochondral lesions of the talus (OLT) may be associated in up to 24% of cases and must be treated concomitantly. We present a 27-year-old male patient with chronic ankle pain and a history of recurrent sprains since childhood. Imaging exams showed malformation of TFS associated with an OLT. He was submitted to surgical treatment with open repair, TFS fixation with suture-button, and osteochondroplasty of the OLT with collagen membrane through arthroscopy. At 13 months follow-up, he was asymptomatic and fully active.